Long-term saline water irrigation affected soil carbon and nitrogen cycling functional profiles in the cotton field - Zhou, Shuang; Wang, Guangshuai; Han, Qisheng; Zhang, Junpeng; Dang, Hongkai; Ning, Huifeng; Gao, Yang; Sun, Jingsheng (Frontiers in Microbiology, 2024)
Saline water irrigation (SWI) plays an important role in alleviating water resource shortages. At the same time, the salt input of irrigation water affects soil microorganisms which participate in various ecological processes of terrestrial ecosystems. However, the responses of soil microbial functional potential to long-term SWI remains unclear. Therefore, metagenomics was employed in cotton fields under long-term SWI, which unveils soil carbon and nitrogen cycles microbial functional profiles. Results indicated that SWI impacted the microbial functional profiles of soil carbon and nitrogen cycles in the cotton fields significantly. Especially, irrigation water salinity inhibited the relative abundances of sacC and vanB, which are soil carbon degradation genes. SWI also affected the functional gene abundance of nitrogen degradation, dissimilatory nitrate reduction, and nitrification. Moreover, SWI significantly increased the abundance of Candidatus_Cloacimonetes in both carbon and nitrogen cycles. Person analysis showed that soil salinity, pH, and ammonium nitrogen were important factors affecting the abundance of functional genes and microbial taxa. In addition, there were synergetic or antagonistic interactions of carbon and nitrogen metabolic potentials through co-occurring network analysis. Overall, this study indicated that long-term SWI significantly influenced specific microbial functional genes and taxa abundance, which may lead to predictable outcomes for soil carbon and nitrogen cycling, and is of great importance in exploring the impact of SWI on soil environments.